A comparative assessment of the immunomodulatory effects of Chromolaena odorata (Lf.) King & Robinson (ASTERACEAE) and Uncaria perrottetii (A. Rich) Merr. (RUBIACEAE) crude extracts in Balb/C mice - Nudo, Leonora P.; Catap, Elene S. (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2009)
The ethanolic extract from Chromolaena odorata (Lf.) King & Robinson leaves and the aqueous extract from Uncaria perrottetii (A. Rich) Merr. vinebark were evaluated for immunomodulating activity on Balb/C mice. Initially, the immunomodulatory potential of each plant extract was evaluated by employing a number of in vitro immune response assays using different concentrations of the plant extracts (10 μg/ml, 20 μg/ml, 50 μg/ml, and 100 μg/ml).
Thesis (M.S. Biology)--University of the Philippines Diliman
Keywords: Herbs -- Therapeutic use -- Philippines